The Study of Formation Characteristics and Development Tendencies of International Information and Knowledge Economy - Alguliyev, Rasim Mahammad; Aliyev, Alovsat Garaja; Abbasova, Vusala Alovsat (Review of Knowledge Economy, 2017)
In this article the characteristics and formation stages of worldwide economical systems are explained. Differences of forming of information, industry and knowledge economy categories are given; approaches to its essence and content are analyzed. Characteristics of information and knowledge, their transformation methods and management systems are investigated. On the base of the analysis of development tendencies and formation characteristics of information and knowledge economy, proper recommendations are given.